Recruitment of integrin α ν β 3 to integrin α 5 β 1 -induced clusters enables focal adhesion maturation and cell spreading - Diaz, Carolina (2019)
The major fibronectin (FN)-binding α5β1 and αvβ3 integrins exhibit cooperativity during cell adhesion, migration and mechanosensing, through mechanisms that are not yet fully resolved. Exploiting mechanically tunable nano-patterned substrates, and peptidomimetic ligands designed to selectively bind corresponding integrins, we report that focal adhesions (FAs) of endothelial cells assembled on α5β1 integrin-selective substrates rapidly recruit αvβ3 integrins, but not vice versa. Blocking of αvβ3 integrin hindered FA maturation and cell spreading on α5β1 integrin-selective substrates, indicating a mechanism dependent on extracellular ligand binding and highlighting the requirement of αvβ3 integrin engagement for efficient adhesion. Recruitment of αvβ3 integrins additionally occurred on hydrogel substrates of varying mechanical properties, above a threshold stiffness that supports FA formation. Mechanistic studies revealed the need for soluble factors present in serum to allow recruitment, and excluded exogenous, or endogenous, FN as the ligand responsible for αvβ3 integrin accumulation to adhesion clusters. Our findings highlight a novel mechanism of integrin cooperation and a critical role for αvβ3 integrins in promoting cell adhesion on α5β1 integrin-selective substrates.